Characterization of the 3′ Termini of the RNAs of Cowpea Mosaic Virus - Steele, Kathleen P. (1978)
A sequence of polyadenylic acid, homogeneous in composition but heterogeneous in length, was isolated from complete pancreatic RNase digests of both middle and bottom RNAs of cowpea mosaic virus. The polyadenylic acid was 3′-terminal and occurred once per molecule. A fragment consisting of the polyadenylic acid and approximately the next 25 nucleotides could be isolated from complete T1 RNase digests of either RNA. The region adjacent to the polyadenylic acid in both RNAs was rich in pyrimidines. The mobilities of the fragments in 12.4% polyacrylamide-8 M urea gels were used to estimate their lengths and to calculate number average and weight average molecular weights.